Very high cycle fatigue strength and crack growth of thin steel sheets (Fracture and Structural Integrity, 2016)
For basic observations or for industrial applications it is of interest to use flat specimens at very high frequency in the gigacycle regime. In this work, thin flat sheet, with 1.2 mm thickness of a complex phase ferrite-martensitic steels were considered for carrying out fatigue tests at high frequency (20 kHz) up to the gigacycle regime (>109 cycles). The crack initiation tests were carried out with water cooling, while the crack growth test were carried out in laboratory air at room temperature. All the tests were carried out under loading ratio R=-1. To do that, special designs of specimens were made and computed using FEM for defining the stress amplitude for endurance tests. Special attachments for specimens to the ultrasonic system’s horn were enhanced. A particular FEM computing of the stress intensity range on crack growth specimens was carried out for determining the specimen dimensions and an equation that defines the stress intensity range as a function of the harmonic displacement amplitude, dynamic Young’s modulus, material density and crack length. Detailed procedures and fatigue results are presented in this paper.
Keywords: Ultrasonic fatigue; Plate steel fatigue; Fatigue resistance; Fatigue crack growth